2021
DOI: 10.3390/informatics8030051
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Habits during COVID-19 Confinement: An Exploratory Analysis from Portugal

Abstract: COVID-19 pandemic consequences are tragic, and many problems will persist after the health problem ends. Some studies have focused on mental health issues, reporting worrying percentages. It is known that there is a bidirectional relationship between mental health and sleep quality, and it would be expected that sleep would be affected by the pandemic. In order to know the Portuguese people’s habits before and during the confinement, we carried out a survey of 188 people aged 13 to 84 (38 ± 15) to find out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Although several studies aiming to assess the sleep quality of nurses and the general population throughout the COVID-19 pandemic have been conducted, few studies have compared the sleep quality of nurses and the general population in the same timeframe and using the same measures. In Portugal, some studies were carried out concerning sleep habits and sleep quality during the COVID-19 pandemic, such as those conducted by Silva and Sobral [ 19 ] and by Paiva et al [ 20 ]. However, none of these allowed us to compare, in a large sample and during the same timeframe, the sleep quality of nurses and the general population, which, according to the findings of the abovementioned studies [ 15 , 17 ], seemed to evolve differently throughout the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies aiming to assess the sleep quality of nurses and the general population throughout the COVID-19 pandemic have been conducted, few studies have compared the sleep quality of nurses and the general population in the same timeframe and using the same measures. In Portugal, some studies were carried out concerning sleep habits and sleep quality during the COVID-19 pandemic, such as those conducted by Silva and Sobral [ 19 ] and by Paiva et al [ 20 ]. However, none of these allowed us to compare, in a large sample and during the same timeframe, the sleep quality of nurses and the general population, which, according to the findings of the abovementioned studies [ 15 , 17 ], seemed to evolve differently throughout the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, Koç and Koç (2021) found a negative effect of the pandemic on learners' extracurricular activities (ECA) and socialization. Some studies reported increased sleeping duration of students during the lockdown (Biswas et al, 2021; Joshi et al, 2020; Marelli et al, 2021), whereas variations were found in sleeping and waking up time in the pandemic period (Genta et al, 2021; Silva & Sobral, 2021). Yoga was found to be a major ECA activity among the medical students (Joshi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies, including a multicenter study (Trakada et al, 2020), have found that respondents tend to sleep substantially more but have poorer sleep quality compared with the prepandemic situation (Fränkl et al, 2021; Gorgoni et al, 2021; Gualano et al, 2020; Gupta et al, 2020; Paiva et al, 2021; Pesonen et al, 2020). Among sleep issues, an increase in nocturnal awakenings (Paiva et al, 2021; Pesonen et al, 2020; Pinto-Silva & Rolland-Sobral, 2021) and moderate or severe insomnia (Gualano et al, 2020; Paiva et al, 2021; Pinto-Silva & Rolland-Sobral, 2021) were reported. Sleep problems were observed predominantly in women (Gualano et al, 2020; Paiva et al, 2021; Pinto-Silva & Rolland-Sobral, 2021), employed people, and students, the latter complaining of difficulty falling asleep and changes in sleep–wake cycles (Paiva et al, 2021; Pinto-Silva & Rolland-Sobral, 2021).…”
mentioning
confidence: 99%
“…Several studies have also reported significant changes in oneiric activity during the pandemic, with an average increase in nightmares (Fränkl et al, 2021; Paiva et al, 2021; Pesonen et al, 2020; Pinto-Silva & Rolland-Sobral, 2021) and dream recall (Fränkl et al, 2021; Giovanardi et al, 2022). In addition, increased dream recall was more common among women (Giovanardi et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation